1989
DOI: 10.1021/bi00440a007
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic study of wild-type and mutant dihydrofolate reductases from Lactobacillus casei

Abstract: A kinetic scheme is presented for Lactobacillus casei dihydrofolate reductase that predicts steady-state kinetic parameters. This scheme was derived from measuring association and dissociation rate constants and pre-steady-state transients by using stopped-flow fluorescence and absorbance spectroscopy. Two major features of this kinetic scheme are the following: (i) product dissociation is the rate-limiting step for steady-state turnover at low pH and follows a specific, preferred pathway in which tetrahydrofo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
2
2

Year Published

1993
1993
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 39 publications
4
65
2
2
Order By: Relevance
“…31 Another ligand, the tetrahydrofolate analogue 5-formyl-5,6,7,8-tetrahydrofolic acid (folinic acid), binds to DHFR with strong negative co-operativity in the presence of NADPH: 32 similar negative co-operativity binding effects have important implications in the control of product release in the enzyme reaction mechanism. 33 The detailed origins of positive and negative co-operative ligand binding are still poorly understood. One possible explanation calls for the first ligand to induce conformational changes in the protein that produce an altered binding environment for the second ligand.…”
Section: Introductionmentioning
confidence: 99%
“…31 Another ligand, the tetrahydrofolate analogue 5-formyl-5,6,7,8-tetrahydrofolic acid (folinic acid), binds to DHFR with strong negative co-operativity in the presence of NADPH: 32 similar negative co-operativity binding effects have important implications in the control of product release in the enzyme reaction mechanism. 33 The detailed origins of positive and negative co-operative ligand binding are still poorly understood. One possible explanation calls for the first ligand to induce conformational changes in the protein that produce an altered binding environment for the second ligand.…”
Section: Introductionmentioning
confidence: 99%
“…While the sequence homology between different vertebrate dhfrs is high (73 to 90%), that between the enzymes from Lactobacillus casei and Escherichia coli is only about 26%. Nonetheless, the overall backbone folds for the two bacterial enzymes, as judged from the crystal structures, are almost identical (Kraut & Matthews, 1987), as indeed are their kinetic mechanisms (Andrews et al, 1989). Notwithstanding these extensive studies of dhfr, a number of aspects of its function are still not completely understood, notably the details of the catalytic mechanism (Basran et al, 1995 and references therein) and the mechanism(s) underlying the effects of substrate analogues on the binding of coenzymes and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…see Neet, 1995 and references therein). There is also a marked negative cooperativity between NADPH and the product tetrahydrofolate (FH 4 ) or its stable 5-formyl analogue (Birdsall et al, 1981), the increased rate of dissociation of FH 4 from the enzyme-NADPH-FH 4 complex as compared to the enzyme-FH 4 complex being an important feature of the kinetic mechanisms of both the L. casei and E. coli enzymes (Fierke et al, 1987;Andrews et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Benkovic et al [28,29,56,57] and Blakley et al [58] have also carried out extensive kinetic studies on several DHFRs. For example, Andrews, Benkovic, and co-workers [56] have shown that for the L. casei enzyme, the dissociation of the product is the rate-limiting step for the steady-state turnover at low pH values.…”
Section: C-andmentioning
confidence: 99%
“…For example, Andrews, Benkovic, and co-workers [56] have shown that for the L. casei enzyme, the dissociation of the product is the rate-limiting step for the steady-state turnover at low pH values. The product, tetrahydrofolate, only dissociates from the enzyme after NADP is replaced by NADPH.…”
Section: C-andmentioning
confidence: 99%